1989
DOI: 10.3109/01485018908986755
|View full text |Cite
|
Sign up to set email alerts
|

Blood Serotonin Levels and Male Infertility

Abstract: Seventy men, aged 20-40 years, who were attending an infertility clinic were studied to evaluate associations between seminal quality, whole blood serotonin, and serum testosterone levels. Men with blood serotonin levels greater than 100 ng/ml showed lower sperm counts and sperm motility than those with normal levels of blood serotonin (less than 90 ng/ml). Seminal volume, pH, sperm morphology, fructose, citric acid, and serum testosterone values were similar between groups of patients with different levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…These differences in reproductive outcome for males differing in CSF 5-HIAA could not be explained by variability in sperm quantity or quality. Whereas previous studies found a relationship between sperm motility and density and urinary 5-HIAA and blood serotonin [Segal et al, 1975;Caldamone et al, 1980;Gonzales et al, 1989Gonzales et al, , 1992, we did not find evidence of an association between CSF 5-HIAA and either sperm measure. As the bulk of urinary 5-HIAA is peripheral in origin, and CSF 5-HIAA reflects a CNS measure, differences between the previous studies showing serotonin influences on sperm qualities and the current study may be a result of where the serotonin metabolites were sampled from, with peripheral serotonin more involved in sperm regulation than CNS serotonin functioning.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These differences in reproductive outcome for males differing in CSF 5-HIAA could not be explained by variability in sperm quantity or quality. Whereas previous studies found a relationship between sperm motility and density and urinary 5-HIAA and blood serotonin [Segal et al, 1975;Caldamone et al, 1980;Gonzales et al, 1989Gonzales et al, , 1992, we did not find evidence of an association between CSF 5-HIAA and either sperm measure. As the bulk of urinary 5-HIAA is peripheral in origin, and CSF 5-HIAA reflects a CNS measure, differences between the previous studies showing serotonin influences on sperm qualities and the current study may be a result of where the serotonin metabolites were sampled from, with peripheral serotonin more involved in sperm regulation than CNS serotonin functioning.…”
Section: Discussioncontrasting
confidence: 56%
“…Specifically, an early study showed that oligospermic and azoospermic men were more likely to exhibit high concentrations of urinary 5-HIAA [Segal et al, 1975]. Another investigation found that men with abnormally high blood serotonin levels produced lower sperm counts and sperm motility [Gonzales et al, 1989[Gonzales et al, , 1992. Even more compelling evidence connecting serotonergic function with semen quality comes from experiments in which dogs induced with a varicocele, a testicular disorder linked with infertility, produced sperm with less motility and higher blood plasma serotonin levels following alteration [Caldamone et al, 1980].…”
Section: Introductionmentioning
confidence: 99%
“…A subject was considered asthenozoospermic if the semen sample had < 60% motile sperm or < 30% sperm with excellent motility. As the prevalence of asthenozoospermia obtained after evaluation of the sperm motility at 2 h is almost the same as that obtained after 4 h (Gonzales, 1985), and as subjects who have normal motility at 2 h maintain this at 4 h (Bilgeri et al, 1987;Mandal & Bhattacharyya, 1987) we have used values at 4 h to correlate sperm motility with corrected values of seminal fructose assayed at the same time.…”
Section: Semen Analysismentioning
confidence: 97%
“…Daily injections of 5-HT precursor (5-hydroxytryptophan (5-HTP)) alter reproductive development and age-dependent body weight gain in mice, accompanied by a low testosterone level and highly reduced sperm counts, motility, and viability (Sethi & Chaturvedi 2009). In addition, studies in humans reported that hyperserotonemia derives in azoospermia (Gonzales et al 1989(Gonzales et al , 1992. Furthermore, in reproductive pathologies such as varicocele, 5-HT blood levels are elevated and it has also been proven that serotoninergic neurotransmission dysfunctions are involved in premature ejaculation (de Jong et al 2006, Chan et al 2008, Motofei 2008.…”
Section: Introductionmentioning
confidence: 99%